Subinhibitory antibiotic concentrations promote the horizontal transfer of plasmid-borne resistance genes from Klebsiellae pneumoniae to Escherichia coli - Ding, Manlin; Ye, Zi; Liu, Lu; Wang, Wei; Chen, Qiao; Zhang, Feiyang; Wang, Ying; Sjöling, Åsa; Martín-Rodríguez, Alberto J.; Hu, Renjing; Chen, Wenbi; Zhou, Yingshun (Frontiers in Microbiology, 2022)
Horizontal gene transfer plays an important role in the spread of antibiotic resistance, in which plasmid-mediated conjugation transfer is the most important mechanism. While sub-minimal inhibitory concentrations (sub-MIC) of antibiotics could promote conjugation frequency, the mechanism by which sub-MIC of antibiotics affect conjugation frequency is not clear. Here, we used Klebsiella pneumoniae SW1780 carrying the multi-drug resistance plasmid pSW1780-KPC as the donor strain, to investigate the effects of sub-MIC of meropenem (MEM), ciprofloxacin (CIP), cefotaxime (CTX) and amikacin (AK) on conjugational transfer of pSW1780-KPC from SW1780 to Escherichia coli J53. The results showed that the transfer frequencies were significantly increased by treating SW1780 strain with sub-MIC levels of MEM, CIP, CTX and AK. Transfer frequencies at sub-MIC conditions in a Galleria mellonella were significantly higher than in vitro. To investigate gene expression and metabolic effects, RT-qPCR and LC-MS system metabolome sequencing were performed. Transcript levels of T4SS genes virB1, virB2, virB4, virB8, conjugation-related genes traB, traK, traE and traL were significantly upregulated by exposure to sub-MIC of MEM, CIP, CTX and AK. Analysis of the results of metabolome sequencing revealed 9 differentially regulated metabolites. Our findings are an early warning for a wide assessment of the roles of sub-MIC antibiotics in the spread of antibiotic resistance.